Development of pH-meter monitoring system using Arduino: article / Mohd Fadhil Ibrahim - Ibrahim, Mohd Fadhil (2012)
This paperwork presents the complete circuit used to interface a pH-meter using Arduino. The objective of study is to investigate the accuracy of the pH-meter using Arduino as a microcontroller. The study focused on the accuracy of phmeter when tested to specified ph buffer. The pH-meter is tested to 4 difference pH buffer to determine the accuracy of this pH –meter. The result shows that this pH-meter has an accuracy of 97% compare to an average pH meter that is about 99% of error. As a conclusion, this pH-meter is very good because the error is below 10%.